Differential cholinergic regulation of dopamine release in the dorsal and ventral neostriatum of the rat: an in vivo microdialysis study - O'Connor, WT (J Neurosci, 1995)
We used in vivo microdialysis to investigate the effects of local perfusion with the AChE inhibitor neostigmine on the basal and haloperidol evoked increase in dialysate dopamine levels in the dorsolateral and fundus striata of the bilaterally implanted halothane anaesthetized rat. In the absence of neostigmine basal dopamine was consistently higher in the dorsolateral striatum compared with the fundus striati. Local perfusion with neostigmine (10 and 100 microM) increased basal dopamine in the fundus striati compared to the contralateral (control) side but not in the dorsolateral striatum. In the absence of neostigmine haloperidol (0.05–0.5 mg/kg, s.c.) increased dopamine release in both the dorsolateral and fundus striata. However, local perfusion with neostigmine (10 microM) attenuated this increase in the dorsolateral striatum at all doses of haloperidol while only the effect of the highest (0.5 mg/kg) dose of haloperidol was counteracted in the fundus striati. Both the basal and haloperidol (0.25 mg/kg) induced increase in dopamine release in the control (no neostigmine) and neostigmine (+10 microM) treated dorsolateral striata were abolished following local perfusion with tetrodotoxin (1 microM). The data demonstrate that the introduction of neostigmine into the neostriatum selectively increases basal DNA levels in the fundus striati and strongly counteracts the haloperidol evoked DA release in the dorsolateral striatum and thus provide strong evidence for a differential cholinergic regulation of striatal DA release in vivo. In addition, we demonstrate that the stimulatory and inhibitory effects of neostigmine operate independently and have a regional specificity within the neostriatum.